MEMBANGUN PERILAKU SANTUN SISWA DALAM TINDAK TUTUR ASERTIF PADA SISWA DI SEKOLAH - Putri, Qikka Anisya Ade; Rustinar, Eli; Mahdijaya, Mahdijaya; Kusmiarti, Reni; Kusumaningsih, Dewi (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to strengthen the renewal of the concept of polite behavior for students in class 7 Indonesian language learning at SMPN 17 Bengkulu City. Thus, the aim of this research is to describe the types of polite behavior of students in learning Indonesian, along with the continuity of these speech acts. The problems in this research are: 1) what are the teacher's assertive speech acts in the 7th grade Indonesian language learning process at SMP Negeri 17 Bengkulu City, 2) what are the uses of assertive speech acts carried out at school, and 3) is there any use of assertive speech acts in behavior? polite students at SMPN 17 Bengkulu City. This research was carried out from 28 August 2023 to 29 August 2023. The data sources in this research were informants, namely teachers and students and incidents of polite behavior in class 7 when learning Indonesian. This research uses data collection techniques. The data collection used in this research is a study of research information or data obtained from photos, sound recordings and videos. Based on the research results, it can be concluded that polite behavior in learning is very important to improve teachers' polite behavior in assertive speech acts among students at school